Jenis dan Sebaran Reptil di Sungai Salawai Negeri Sawai Kecamatan Seram Utara Kabupaten Maluku Tengah - Sitohang, Edo V; Badaruddin, Eernytwati; Tuhumury, Andre (Jurnal Agrosilvopasture-Tech, 2024)
River border conditions that support community activities in utilizing natural resources greatly affect habitat conditions for creatures living around river boundaries, especially reptiles. This study aims to determine the type and distribution of reptiles in the Salawai River, Sawai State, North Seram District, Central Maluku Regency. The procedure for taking reptile data that will be carried out is to apply the census method, namely a direct census is data collection carried out directly in the field on each research plot, namely recording all types of reptiles found. Indirect census is data collection carried out through the discovery of body parts left by reptiles such as scales (skin), bones, eggshells. Discovery of traces of animal activities such as former nests, feed marks, scratch marks on tree trunks with footprints. Based on the results of observations made in the Salawai River, which includes 3 observation blocks, 9 species of reptiles belonging to 6 families, and 2 orders. Saltwater crocodile (Crocodylus porosus), Moluccan monitor lizard (Varanus indicus), Panana lizard (Tiliqua gigas evanescens), Common sun skink (Eutropis multifasciata), Blue-tailed lizard (Cryptoblepharus egeriae), green-crested chameleon (Bronchocela cristatella), Kalamar snake (Calamaria ceramensis), python (Morelia amethistina), common bronzeback (Dendrelaphis pictus). Land use activities by local communities affect habitat degradation due to damage to forest structure, thus affecting the distribution and abundance of reptiles.